Dry Arthroscopy Distal Radioulnar Joint and Foveal Insertion: Surgical Technique - Ecker, Jeff; Andrijich, Courtney (Journal of Wrist Surgery, 2021)
Background Arthroscopy of the distal radioulnar joint is considered to be difficult to perform. At this time the integrity of the foveal insertion is indirectly evaluated with a hook test. If a hook test is positive it is inferred that the foveal insertion is torn or incompetent.Description of Technique The ideal way to evaluate the foveal insertion is by direct visualization and probing. In order to do this, arthroscopic examination of the distal radioulnar joint and foveal insertion is required. The article describes how to reliably perform “dry” arthroscopy of the distal radioulnar joint and foveal insertion using a 1.9 mm arthroscope to accurately assess the triangular fibrocartilage complex and foveal insertion.Patient and Methods A total of 169 dry DRUJ arthroscopies were performed by the primary author between January 2018 and February 2021.Results Using this technique, the foveal insertion was successfully visualized in 168 cases (99%).Conclusion Dry arthroscopy of the DRUJ is a reliable technique to evaluate the integrity of the foveal insertion.
Keywords: dry arthroscopy; distal radioulnar joint; triangular fibrocartilage; foveal insertion; wrist